ANALISIS YURIDIS MENGENAI AKIBAT HUKUM TERHADAP PERUSAHAAN PAILIT YANG TIDAK MELAKUKAN JAMINAN BELI KEMBALI DALAM HUKUM BISNIS - Helfira Citra; Elwidarifa Marwenny; Sry Wahyuni; Fatima Zahra Noer Hermansyah (Ensiklopedia Research and Community Service Review, 2026)
This research aims to analyze the legal position of bankrupt companies that do not provide buy-back guarantees as preferred creditors and examine the legal consequences that arise in bankruptcy practice. The background of this research is that company bankruptcy causes fundamental changes to the legal position of companies and even workers/laborers, from subjects of employment relations to creditors in the bankruptcy process. In the Indonesian legal system, companies are recognized as preferred creditors who have priority rights to payment of wages and other normative rights because wages are alimentary and are the main source of livelihood for workers and their families. This research uses a descriptive qualitative method with a library research approach, namely by reviewing various classical and contemporary literature related to the concept of the Company in business law. Data sources were obtained from the Civil Code, laws (especially the Company Law (UU No. 1 of 1995) and the Bankruptcy Law), as well as scientific journals. The research results show that harmonization of regulations and strengthening of protection mechanisms is needed to ensure the fulfillment of the principles of legal certainty and social justice in business law. The conclusion of this research confirms that the application of legal certainty in company law is the key to achieving balance and success. Keywords:  Company, Bancrupt and Buyback